2013
DOI: 10.1002/btpr.1820
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to achieving modular retrovirus clearance for a parvovirus filter

Abstract: Viral filtration is routinely incorporated into the downstream purification processes for the production of biologics produced in mammalian cell cultures (MCC) to remove potential viral contaminants. In recent years, the use of retentive filters designed for retaining parvovirus (~20 nm) has become an industry standard in a conscious effort to further improve product safety. Since retentive filters remove viruses primarily by the size exclusion mechanism, it is expected that filters designed for parvovirus rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Previously identified gaps are extreme flux decay and virus overloading . Recently, fluid flow interruptions (FFI) have been identified as a technical vulnerability for more than one type of small virus retentive filters . Recent work has also established that the magnitude of low pressure or FFI impacts on small virus retention are both product and process‐specific .…”
Section: Introductionmentioning
confidence: 99%
“…Previously identified gaps are extreme flux decay and virus overloading . Recently, fluid flow interruptions (FFI) have been identified as a technical vulnerability for more than one type of small virus retentive filters . Recent work has also established that the magnitude of low pressure or FFI impacts on small virus retention are both product and process‐specific .…”
Section: Introductionmentioning
confidence: 99%
“…retroviruses are of a sufficiently large size that they would be effectively removed by either of the filter types tested. Filters with an even smaller pore size, i.e., 20 nm, have been shown to consistently remove retroviruses to undetectable levels from a range of different cell derived products . Where the removal of smaller viruses is important, filter selection/mode of action becomes more critical .…”
Section: Discussionmentioning
confidence: 99%
“…As filters remove viruses predominantly by a size‐exclusion mechanism, large viruses should be completely retained with the use of a small virus retentive filter . Stuckey et al have demonstrated that MuLV is completely retained by small virus filters even when significant parvovirus breakthrough is observed in co‐spiking experiments . An industry‐wide evaluation of small virus retentive filters also found that large enveloped viruses were reduced below the limit of detection in all 198 cases examined, providing additional rationale that viral testing only needs to be performed with smaller virus as a worst case scenario .…”
Section: Scientific and Technology Considerationsmentioning
confidence: 99%